Shape memory thermoplastic natural rubber for novel splint applications - N. Lehman; L. Songtipya; J. Johns; K. Maliwankul; S. P. Voravuthikunchai; Y. Nakaramontri; K. Sengloyluan; E. Kalkornsurapranee (eXPRESS Polymer Letters, 2021)
Shape memory polymer (SMP) based on thermoplastic natural rubber (TPNR) for soft-touch splint application has been successfully developed. The main aim was to investigate the proper phase combination between thermoplastic (i.e., polycaprolactone (PCL)) and rubbers materials. Different types of rubbers, namely natural rubber (NR) and epoxidized natural rubber (ENR), were used as the rubber phases in the SMP-TPNR. Mechanical properties, shape memorial efficiency, swelling, and morphologies of the resulting material were examined. The tensile strength and hardness of the SMP-TPNR were found to be increased by using polar ENR as the rubber phase. Better compatibility between ENR and PCL molecular chains lead the material to achieve significant improvement in the shape memory behavior compared to the one with unmodified NR. The main advantage of polar rubber is its great opportunity to apply the material for splint fixing applications. On comparing with various commercially available materials (i.e., plaster, fiberglass, aluminum with foam and commercial thermoplastic splint), the developed SMP-TPNR material exhibited better performances in terms of ease of processing, costeffectiveness, comfortability (soft-touch), water resistance and impact resistance.